Simulação fluidodinâmica de um leito fluidizado empregando correlações de arrasto gás-sólido ajustadas por valores experimentais - Kestering, Daniel Augusto (Universidade do Vale do Rio dos Sinos, 2016)
The investigation of gas-solid drag models is a key to obtain good results of fluidization by using computational fluid dynamic tools. The fluidization technology is used for solid fuel thermal conversion and its main advantage is the high gas-solid mixture. The present effort uses two software for fluidized beds simulation, MFIX and Ansys Fluent, in order to compare the drag models of Syamlal and O`Brien (1987) and Di Felice (1994). Two Fluid Model is the approach used to model together with Kinetic Theory for Granular flow. A method to adjust DF drag model (DI FELICE, 1994), based on Esmaili and Mahinpey (2011), is suggested, as well as SO drag model (SYAMLAL; O’BRIEN, 1987) is adjusted using data obtained from minimum fluidization condition. Experiments were realized to obtain velocity and void fraction at minimum fluidization condition in order to adjust both models. Glass beads with diameter of 1,21 mm and 0,8 mm and sand with diameter of 0,29 mm were used on experiments. The purposed method fits the data obtained on minimum fluidization condition of the three particles, in accordance with experimental data. With the models adjusted, numerical simulation were conducted using drag models for two- and three-dimensional domain. The results of this simulations agrees with experimental data of pressure drop and bubble formation. Simultaneously, a code to obtain a drag model using EMM/Bubbling algorithm was developed and numerical simulation were conducted. Results of EMMS show that the model have the same tendency of results of Shi, Wand and Li (2011), who developed EMMS/Bubbling model.
Keywords: CFD.Dinâmica de fluidos computacional; EMMS/bubbling; Ajuste de modelo de arrasto gás-sólido; CFD. Computational fluid dynamic; Gas-solid drag model adjustment; ACCNPQ::Engenharias::Engenharia Mecânica